2017
DOI: 10.7759/cureus.1248
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Barriers to Lung Cancer Screening in Karachi, Pakistan: A Cross-Sectional Survey of Smokers and Physicians

Abstract: BackgroundEarly detection of lung cancer using low-dose computed tomography (LDCT) can potentially reduce morbidity and mortality. However, LDCT for lung cancer screening, especially in low income countries, has been underutilized. The objective of this study was to evaluate the prevalence and the potential personal, social, and economic barriers of lung cancer screening using LDCT.MethodsA total sample of 156 smokers and 200 general physicians was collected during December 2016-February 2017 from community se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Hence, in addition to building infrastructure that equitably reaches the population in the long term, the employment of mobile CT scanners and one-stop 'lung health-checks' among community centers 60 , as well as the provision of complementary transportation within screening programs, are essential strategies to address such scenarios 61 . Moreover, physician unawareness of screening guidelines and lack of time for counseling represent challenges for the identification and adherence of eligible high-risk individuals in LMICs 62,63 . For instance, in Egypt, a national pilot survey demonstrated that physicians do not frequently perform LCS, notwithstanding expert group recommendations 64 .…”
Section: Screening Delivery In Lmicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, in addition to building infrastructure that equitably reaches the population in the long term, the employment of mobile CT scanners and one-stop 'lung health-checks' among community centers 60 , as well as the provision of complementary transportation within screening programs, are essential strategies to address such scenarios 61 . Moreover, physician unawareness of screening guidelines and lack of time for counseling represent challenges for the identification and adherence of eligible high-risk individuals in LMICs 62,63 . For instance, in Egypt, a national pilot survey demonstrated that physicians do not frequently perform LCS, notwithstanding expert group recommendations 64 .…”
Section: Screening Delivery In Lmicsmentioning
confidence: 99%
“…For instance, in Egypt, a national pilot survey demonstrated that physicians do not frequently perform LCS, notwithstanding expert group recommendations 64 . In Pakistan, a sample survey of 200 primary care physicians revealed that even though 54.5% acknowledged the effectiveness of LCS, only 33.3% reported ordering the test 63 . Furthermore, counseling has a significant impact on screening adherence, as corroborated by a study among Korean men showing that physician discussions with patients regarding the harms and benefits of LDCT screening improved participation from 10.6% to 95.1% (ref.…”
Section: Screening Delivery In Lmicsmentioning
confidence: 99%
See 3 more Smart Citations